Exploring Variances of White Matter Integrity and the Glymphatic System in Simple Febrile Seizures and Epilepsy - Salimeen, Mustafa Salimeen Abdelkareem; Liu, Congcong; Li, Xianjun; Wang, Miaomiao; Singh, Martha; Si, Shuqing; Li, Mengxuan; Cheng, Yannan; Wang, Xiaoyu; Zhao, Huifang; Wu, Fan; Zhang, Yuli; et al. (Frontiers in Neurology, 2021)
Background Simple febrile seizures (SFS) and epilepsy are common seizures in childhood. But SFS mechanism is uncertain and whether there exist obviously variances of white matter (WM) integrity and glymphatic function between SFS and epilepsy is unclear. Therefore, this study aims to investigate variances of WM integrity and glymphatic function in SFS and epilepsy. Material and Methods We retrospectively included 26 children with SFS, 33 children with epilepsy and 28 controls aged 6–60 months with MRI. TBSS was used to compare DTI metrics of WM among above groups. T2WI were used to segment visible VRS through a custom-designed automated-method. VRS counts and volume were quantified and compared among SFS, epilepsy and control groups. Correlations of VRS metric and seizure duration and course after seizure onset were also investigated. Results Comparing with controls, no significant change of fractional anisotropy (FA), axial diffusivity (AD) or radial diffusivity (RD) in WM of children with SFS was found (P>0.05). Decreased FA, unchanged AD and increased RD were observed in epilepsy group compared with SFS, controls (P<0.05). Meanwhile, VRS counts were higher in SFS and epilepsy than controls (VRS_SFS, 442.42±74.58, VRS_epilepsy, 629.94±106.55, VRS_control, 354.14±106.58; P<0.001), as similar results were found in VRS volume (VRS_SFS, 6228.18±570.74mm3, VRS_epilepsy, 9684.84±7292.66mm3, VRS_control, 4007.22±118.86mm3; P<0.001). But VRS metrics were lower in SFS than epilepsy (P<0.001). in both SFS and epilepsy, VRS metrics were positively correlated with seizure duration and negatively correlated with course after seizure onset. Conclusion: SFS cannot cause WM microstructural disruption, but epilepsy is related to WM alteration. Seizures are associated with glymphatic dysfunction either in SFS or epilepsy.